Literary tradition and the Egyptian Book of the Dead - Berisha, Labinot; Pervorfi, Lorina (Technium Social Sciences Journal, 2022)
The oral literary tradition, which lasted for centuries among different tribes and peoples, preceded the art of the written word, the written literature that was born much later. Thus, written literature was based on the types of oral literature for many important elements of the design of literary works. Of course, writing enabled literature and its types to take a different course and development compared to the creations - works of oral literature, which were passed down orally from one person to another, from one generation to another, and over time many of them were forgotten and disappeared. The poetic language used by the writers in their texts conditioned not only the value of the works they created, but also the way they were accepted and communicated to the recipient not only of the time they were created but also of later times. In the Book of the Dead, Toti, the ruler of heaven, earth, and the underworld, the creator of life and of all nations, says: “I gave breath (air) to him who was in the secret place by the power of the magic words of my discourse, and Osiris triumphed over the enemies”. One of the first forms with literary elements is the Book of the Dead, of Egyptian tradition, consisting of hymns, litany and religious texts and which belongs to the time of the reign of Semt, king of the first Dynasty, which, according to connoisseurs of this work was copied, re-copied and added from generation to generation over a period of close to 5000 years ”. Indeed, the book consists of various creations which the Egyptians wrote on tombs and sarcophagi, on coffins and on immortal slabs, on papyri, talismans and pyramid walls to ensure the well-being of their dead in the afterlife. Works that come to us from a distant past, such as the "Egyptian Book of the Dead", testify, in one way or another, the course of the change of the art of speech over time, the enrichment and importance it has had for man and its existence.